Air dan Kehidupan: Relevansi Ekologi Hindu dalam Menghadapi Krisis Air Bersih di Tengah Modernisasi Bali - Gaduh, Acyutananda Wayan; Widyawati, Anak Agung Ayu Alit (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
The water crisis is an ecological issue currently confronting Bali, even though in Hindu teachings water is regarded as a sacred element symbolizing purity, life, and well-being. Water plays a central role in various ritual practices, which is why Hinduism is often referred to as a Tirtha-based religion. However, rapid tourism development and modernization have fostered a shift in community orientations toward nature, including a diminishing reverence for water sources. This study aims to explore the relevance of Hindu ecological principles in responding to Bali’s water crisis. The research utilizes a qualitative-descriptive approach with philosophical and ecotheological frameworks, integrating Hindu ecological concepts with the perspective of deep ecology. The findings indicate that water holds a central position in the religious and cultural life of Hindu communities in Bali as a symbol of purification, protection, and divine grace. It is emphasized that the sacred value of water can serve as the foundation for ecological ethics in contemporary water resource management. The study's contribution lies in offering a framework of ecological awareness based on spiritual principles that can guide sustainable development policy formulation in Bali. Honoring water from upstream to downstream is essential to maintaining ecological balance. However, population growth and the increasing demands of tourism have intensified the exploitation of water sources, resulting in declining water quality and availability. Thus, Hindu ecology provides a basis for conservation through the application of the Mandala concept, the preservation of Alas Angker (sacred forests) and sacred trees, and the strengthening of the Subak irrigation system. These efforts require individual awareness, support from customary and religious institutions, and strong political will from the government to restore Bali’s natural harmony.